DNA replication stress underpins the vulnerability to oxidative phosphorylation inhibition in colorectal cancer - Xiao Hong Zhao; Man Man Han; Qian Qian Yan; Yi Meng Yue; Kaihong Ye; Yuan Yuan Zhang; Liu Teng; Liang Xu; Xiao-Jing Shi; Ting La; Yu Chen Feng; Ran Xu; et al. (Cell Death and Disease)
Abstract Mitochondrial oxidative phosphorylation (OXPHOS) is a therapeutic vulnerability in glycolysis-deficient cancers. Here we show that inhibiting OXPHOS similarly suppresses the proliferation and tumorigenicity of glycolytically competent colorectal cancer (CRC) cells in vitro and in patient-derived CRC xenografts. While the increased glycolytic activity rapidly replenished the ATP pool, it did not restore the reduced production of aspartate upon OXPHOS inhibition. This shortage in aspartate, in turn, caused nucleotide deficiencies, leading to S phase cell cycle arrest, replication fork stalling, and enrichment of the p53 pathway, manifestations of replication stress. The addition of purine nucleobases adenine and guanine along with the pyrimidine nucleoside uridine restored replication fork progression and cell proliferation, whereas the supplementation of exogenous aspartate recovered the nucleotide pool, demonstrating a causal role of the aspartate shortage in OXPHOS inhibition-induced nucleotide deficiencies and consequently replication stress and reductions in proliferation. Moreover, we demonstrate that glutamic-oxaloacetic transaminase 1 (GOT1) is critical for maintaining the minimum aspartate pool when OXPHOS is inhibited, as knockdown of GOT1 further reduced aspartate levels and rendered CRC cells more sensitive to OXPHOS inhibition both in vitro and in vivo. These results propose GOT1 targeting as a potential avenue to sensitize cancer cells to OXPHOS inhibitors, thus lowering the necessary doses to efficiently inhibit cancer growth while alleviating their adverse effects.